Assessing social determinants of health in a pediatric diabetes clinical research trial: Are recruited subjects representative of the larger clinical population?. (March 2016) - Inman, Mark; Daneman, Denis; Curtis, Jacqueline; Sochett, Etienne; Elia, Yesmino; Dunger, David B.; Deanfield, John; Mahmud, Farid H.
Highlights: Social determinants of health (SDH) may impact diabetes trial outcomes. Effective study design can mitigate the impact of SDH in clinical research. Clinical research trials should be designed to account for relevant SDH. Abstract: Social determinants of health (SDH) impact clinical outcomes and are often poorly described in research trials. Using a validated tool, SDH dimensions were compared between adolescents enrolled and not enrolled into a large diabetes study. We observed that our study cohort reflected a SDH profile mirroring the eligible population.